2022
DOI: 10.1111/petr.14390
|View full text |Cite
|
Sign up to set email alerts
|

Metronidazole for treatment of norovirus in pediatric transplant recipients

Abstract: Background Norovirus is a common cause of gastroenteritis in both immunocompetent and immunocompromised hosts. In transplant recipients, it can lead to prolonged shedding and chronic diarrhea. Treatment with nitazoxanide, oral immunoglobulin, or mammalian target of rapamycin inhibitors has shown varying degrees of benefit in case reports and case series. Prior studies have shown that the commensal gastrointestinal bacterial flora may influence the pathogenesis of norovirus infection. Metronidazole is often use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(21 reference statements)
2
1
0
Order By: Relevance
“…For example, it is possible NTZ could exert indirect antiviral activity via immune cells which are lacking in our current model. However, our data are consistent with several observational clinical studies where no differences were reported between NTZ treatment and other or no treatments in chronically infected HuNoV patients (32,34,35). A recent clinical trial (NCT03395405) aimed to assess NTZ treatment for persons chronically infected with HuNoV but failed to enroll its targeted number of patients because of the COVID-19 pandemic; that said, reported outcomes of the 31 randomized patients suggest that NTZ did not improve clinical resolution of symptoms compared to placebo, with no effect on fecal viral load observed.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For example, it is possible NTZ could exert indirect antiviral activity via immune cells which are lacking in our current model. However, our data are consistent with several observational clinical studies where no differences were reported between NTZ treatment and other or no treatments in chronically infected HuNoV patients (32,34,35). A recent clinical trial (NCT03395405) aimed to assess NTZ treatment for persons chronically infected with HuNoV but failed to enroll its targeted number of patients because of the COVID-19 pandemic; that said, reported outcomes of the 31 randomized patients suggest that NTZ did not improve clinical resolution of symptoms compared to placebo, with no effect on fecal viral load observed.…”
Section: Discussionsupporting
confidence: 92%
“…In most experiments, the EC50 was close in value to the CC50, demonstrating that inhibition of viral replication was largely attributed to its cytotoxicity. Our data are consistent with recent observational clinical studies reporting NTZ's inefficacy for chronically infected HuNoV patients compared to other or no treatments (32,34,35). Thus, HIEs can serve as a valuable preclinical tool to robustly evaluate antivirals for HuNoV infection.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation